The complex trauma of psychological violence: cross-sectional findings from a Cohort of four Danish Women Shelters - Sarah Dokkedahl; Trine Rønde Kristensen; Siobhan Murphy; Ask Elklit (European Journal of Psychotraumatology, 2021)
Background: Psychological trauma has only recently been considered a traumatic event. Therefore, research on Posttraumatic Stress Disorder (PTSD) and Complex-PTSD following exposure to psychological violence, is less studied compared with physical and sexual violence. Objectives: This study aimed to establish the prevalence of PTSD and C-PTSD of among female victims of partner violence (IPV) and examine the unique association between different subtypes of IPV (i.e. physical, psychological and sexual IPV) and the traumatic response. Methods: The study includes a shelter-based sample of female victims of IPV (N = 147). Validated measures were used to estimate IPV exposure and mental health outcomes. Partial Correlation and Hierarchical Regression was used to examine the association between IPV and PTSD and C-PTSD, respectively. Results: The study found a high prevalence of both PTSD (56.5%) and C-PTSD (21.1%) in the sample. Overall, when controlling for the other types of violence, psychological violence correlated with PTSD, C-PTSD, negative affect and somatization. When controlling for psychological violence, neither physical nor sexual violence correlated with any of the mental health outcomes. Hierarchical regression models helped explain 23.5% and 29.7% of the variance in symptoms of PTSD and C-PTSD, respectively. Conclusion: A relatively large subgroup of the women had symptoms of C-PTSD, which demonstrate a potentially unmet need for trauma-informed treatment services in Danish Women Shelters. Psychological violence was found to be the strongest risk factor for all mental health outcomes and thus, it is important to acknowledge the severity of this IPV subtype.